The USE OF AUDIO VISUAL MEDIA IN MATHEMATICS SUBJECTS TO IMPROVE CRITICAL THINKING OF STUDENTS - Wulan Agma Pratiwi, Wulan Agma Pratiwi (The Elementary Journal, 2024)
Students in learning mathematics often only focus on memorizing formulas. This causes students' critical thinking skills to not develop optimally. The ability to think critically is very important for the lives of students because with it students will be able to solve the problems they face by taking or making effective decisions. The purposes of this study are (1) to describe the implementation of audio-visual media in mathematics to improve critical thinking in class 4 MI Podorejo Tulungagung? (2) Describe the inhibiting and supporting factors in the use of audio-visual media to improve critical thinking for class 4 MI Podorejo Tulungagung? (3) Describe the impact of using audio-visual media on increasing critical thinking in class 4 MI Podorejo Tulungagung. This study uses a qualitative approach. The research location is in MI Podorejo Tulungagung. This study uses a qualitative approach. Data collection techniques used are observation, interviews, and documentation. The data validation technique uses source triangulation and technical triangulation methods. The data analysis technique used is Miles and Huberman's data analysis with data condensation steps, data presentation, and drawing conclusions. The results of this study indicate that the implementation of audio-visual media using learning animation videos starts from the teacher preparing the equipment, conditioning the class, and students analyzing the video content, besides that the teacher also uses various methods such as question and answer, demonstrations, lectures. Factors that support the use of audio-visual media are adequate facilities and infrastructure, enthusiastic students, and high teacher professionalism. Meanwhile, the inhibiting factor for using audio-visual media in increasing critical thinking is that students lack self-confidence even though they have the right answers. The impact of using audio-visual media is that students have motivation and to learn so that critical thinking skills and student learning outcomes increase.